2012
DOI: 10.1016/j.neulet.2012.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin regulates brain spontaneous low-frequency brain activity in Neurofibromatosis type 1

Abstract: In the Neurofibromatosis type 1 (NF1) mouse model, lovastatin, used clinically for hypercholesterolemia, improves cognitive dysfunction. While such impairment has been studied in NF1, the neural substrates remain unclear. The aim of this imaging add-on to a phase-1 open-label trial was to examine the effect of lovastatin on Default Network (DN) resting state functional connectivity (RSFC). Seven children with NF1 (aged 11.9±2.2; 1 female) were treated with lovastatin once daily for 12 weeks. A 7-minute 3-Tesla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 32 publications
3
34
1
1
Order By: Relevance
“…A limitation of the current study is the modest size of the patient group, although similar group sizes have been used in other fMRI studies in NF1 (Chabernaud et al, 2012;Violante et al, 2012). Behavioral data were available for only a subset of control subjects, although group differences were very much in line with those observed in earlier studies with larger control samples.…”
Section: Functional Connectivity Changes In Nf1mentioning
confidence: 68%
See 1 more Smart Citation
“…A limitation of the current study is the modest size of the patient group, although similar group sizes have been used in other fMRI studies in NF1 (Chabernaud et al, 2012;Violante et al, 2012). Behavioral data were available for only a subset of control subjects, although group differences were very much in line with those observed in earlier studies with larger control samples.…”
Section: Functional Connectivity Changes In Nf1mentioning
confidence: 68%
“…A number of task-based functional imaging studies showed abnormal activation of brain regions associated with phonological and visual processing, as well as the effect of medication on the DMN (Billingsley et al, 2004;Chabernaud et al, 2012;Clements-Stephens et al, 2008;Violante et al, 2012), all reporting on task-related functional network changes.…”
Section: Introductionmentioning
confidence: 99%
“…While lovastatin is lipophilic and crosses the bloodbrain barrier, it is possible that our dose was not sufficient to produce a therapeutic effect on human brain function. Although indirect evidence of improved memory and functional connectivity from a 12-week phase I study suggests that our dose may have been sufficient to inhibit RAS-mitogen-activated protein kinase activity, 7,8 this small open-label study was not powered for efficacy. Increasing the dose, especially in a pediatric population, would likely increase the risk of AEs, and the effect of statins on hormones critical in sexual development is unknown.…”
mentioning
confidence: 98%
“…While 2 randomized controlled trials of simvastatin reported no treatment effect on cognitive outcomes, 5,6 studies evaluating lovastatin have been more promising. An initial open-label phase I trial of lovastatin demonstrated normalization of functional connectivity within the default mode network 7 with accompanying improvements in memory and attention. 8 More recently, results from a small randomized controlled trial in children and adults with NF1 reported beneficial effects of lovastatin on learning and memory.…”
mentioning
confidence: 99%
See 1 more Smart Citation